The superficial circumflex iliac artery perforator flap in head and neck reconstruction: a retrospective review - James Every; Jeremy Wiseman; Quan Ngo; Michael Kernohan; Chris Ahn (Australasian Journal of Plastic Surgery)
**Introduction**: The superficial circumflex iliac artery perforator flap is a well-established alternative to traditional fasciocutaneous flaps for reconstructive purposes. It is gaining popularity due to short raise time, flap size, ability to provide concurrent raise and donor site concealment. Here we report our initial experience using the superficial circumflex iliac artery perforator flap to reconstruct a variety of defects in the head and neck region.